Effects of three different treatment and rehabilitation programs on quality of life of opiate abusers in Kuala Lumpur and Selangor, Malaysia - Salleh, Mohd Azizi (2016)
Introduction: In 2014, the Malaysian government, through the National Antidrugs Agency (NADA), spent RM 306 million for drug eradication activities in Malaysia. This fund also included the budget for providing the rehabilitation and treatment programs to ensure appropriate management of drug abusers. Among the goals of these programs was to improve the quality of lives of drug abusers so that they will be able to contribute to themselves and the society. Objective: The objective of this study was to compare the changes in the quality of life of opiate abusers who were enrolled in different treatment and rehabilitation programs in Kuala Lumpur and Selangor. Methods: A quasi-experimental was conducted to determine effects of different treatment and rehabilitation programs on the quality of life of three groups of opiate abusers in Kuala Lumpur and Selangor. Group 1 was the Cure & Care program participants in Cure & Care Clinic Sg. Besi, Group 2 was the Methadone Replacement Therapy program participants in Polyclinic Khafidz and Group 3 was the street drug users group in Chow Kit,. Data were collected using self-administered World Health Organization-Quality of Life (WHOQOL-BREF) questionnaire at the time of enrollment into the programs and six months later. Descriptive, bivariate and multivariate analysis were conducted using SPSS version 22. This study was approved by Medical Research Ethics Committee for Research Involving Human, Universiti Putra Malaysia. Results: A total of 141 participants completed the questionnaire. The pre-test and post-test showed that the Cure & Care program participants had better improvement in domains’ scores of quality of life (QOL) namely physical (t=5.183, p=0.001), pscychological (t=8.352, p=0.001), Social Relationship (t=3.651, p=0.003) and Environment (t=4.414, p=0.001) than Methadone Replacement Therapy (MRT) program participants and street drug users who did not undergo any interventions. Educational level had statistically significant association on the score of QOL in physical (F=5.013, p<0.05), social relationship (F=3.652, p<0.05) and environment (χ²=6.014 , p=0.05) for Cure & Care program participants. Educational level also had statistically significant association on the score of QOL among the street drug user in the physical (F=4.511, p<0.05) and environment domains (F=3.508, p<0.05). The religion factor which was Hindu had statistically significant association on the score of QOL in the psychological domain (F=3.720, p<0.05) among MRT program participants at Polyclinic Khafidz. The multivariate linear regression analysis showed that education level was a significant predictor for changes in the QOL scores in the physical, social relationship and environment domains for participants in Cure & Care program and the street drug users. Conclusion: This present study suggests that the Cure & Care Program carried out at Sg. Besi Cure & Care Clinic is better than MRT program at Polyclinic Khafidz and the no-intervention among drug abusers in Chow Kit in terms of improving the quality of life of the opiate drug abusers. The associated and predicting factors identified in this study can provide information to policy makers such as NADA in determining the suitable candidates for the programs to ensure improvement in their quality of life.